Principles of engagement and vision to action for transdisciplinary research and co-design in agroecology - Fuchs, Lisa Elena; Voss, Rachel C.; Freed, Sarah; Rietveld, Anne; Falk, Thomas; Triomphe, Bernard; Bergamini, Nadia; Dickens, Chris; Quintero, Marcela (2025)
Living labs or living landscapes are gaining momentum as sub-national territories within which sustainable food system transformation is sought through multi-stakeholder engagement processes.